Adaptation and Validation of the Beliefs about Medicines Questionnaire (BMQ) in HIV Out-patients in Indonesia - Elfride Irawati Sianturi; Elsye Gunawan; Dyah A. Perwitasari (Universitas Gadjah Mada, 2021)
This study aimed to translate and cross-cultural adapt the version of the Beliefs about Medicines Questionnaire (BMQ) into Indonesia language, and explored its psychometric properties, and establish preliminary norms. We followed the guideline for forward-backward translation and 201 HIV out-patients were recruited. They all completed BMQ-general and BMQ-specific scales that were previously culturally adapted and translated into the Indonesian language. All participants were patients visiting a referral hospital in Papua Province, Indonesia. One-third of participants were indigenous Papuans, and the majority were female. The overall Cronbach's alpha of BMQ was acceptable (0.80) however each domain of BMQ was lower than the original study. The Cronbach alpha value for each section of BMQ-Indonesian version was as follows: BMQ Specific-Necessity 0.56; BMQ Specific-Concerns 0.50; BMQ General-Overuse 0.65; and BMQ General-Harm 0.53. The reasons for the distinction between this study to original may be complex and HIV associates with the problem in neurological and cognitive symptoms at a later stage. Since the Cronbach alpha in this study was within the range of the original study the BMQ-Indonesian version is applicable to be used in Indonesia, especially among HIV patients but caution is still needed in this questionnaire.